Electrocatalysts for Oxygen/Hydrogen-Involved Reactions - Jingqi Guan; Yin Wang (Molecules, 2022)
Oxygen/hydrogen-involved reactions are key reactions in many energy-related technologies, such as electrolytic water, electrocatalytic carbon dioxide reduction, electrochemical ammonia synthesis, rechargeable metal–air batteries, and renewable fuel cells [...]